PERILAKU KEPEMIMPINAN KEPALA DESA DALAM PELAKSANAAN TUGAS DI DESA SERANTAS KECAMATAN PULAU TIGA KABUPATEN NATUNA - Eka Erawan E.21106012 (FISIP Universitas Tanjungpura, 2013)
ThisarticletitledHead ofleadershipbehavior, whichintends to determinehow the behavior leader serantasvillageheadsandemployeesif it isas expected. Because thephenomenonisfoundrarely enteredthe villageheadofficesandemployeeswho come lateaccording tothe appointed hour.Aleadermustbe able tobean exampleorrole model forsubordinates. A leaderis afigurewith authority, responsible, creativeand has abroad knowledgeof theorganization/institutionhe heads. This research isdescriptivequalitativemethod. The research wasconductedat thedistricthead's officeserantasthreeislands. Thevillageheadserantasleadershipbehavioristhe village headinoneworkingweekof work, usuallyonly makestwoorthreedaysrestdoes notcome withouta clear explanation. Behaviorserantasvillageheadoffice employees, employeeswhoarrivelate in the morning, return homeearly, so the timeof service provided tothe community is relativelyshort. Authorrecommendsserantasvillageheadsandemployeescan changebehavior, especiallytofostergoodworking relationshipsandcommunicationis moreopento its employeesandimprovingemployeediscipline, village headsshouldbe firm withemployeeswholack discipline.Keywords: Behaviorleaders, builddiscipline,an examplerole model